2010
DOI: 10.54991/jop.2010.186
|View full text |Cite
|
Sign up to set email alerts
|

Plant fossils of Maitur Formation: possibly the ultimate stage of Glossopteris flora in Raniganj Coalfield, India

Abstract: The present paper deals with the plant megafossil assemblage from the Maitur Formation, the lower part of Panchet Group of rocks, unconformably overlain by coal bearing Raniganj Formation in Raniganj Coalfield, West Bengal. The plant fossils are collected from two localities exposed in Nonia Nala Section near Asansol, Burdwan District, West Bengal. The assemblages are represented by the typical elements of Glossopteris flora, viz. Trizygia speciosa, Neomariopteris hughesii. N. lobifolia, Dichotomopteris lindle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These features are attributed to surface feeding of insect (Labandeira & Phillips, 1996;Srivastava & Agnihotri, 2011). Slater et al (2014) have observed probable presence of external foliage damage and other types of insect herbivory in Indian Gondwana floral assemblages described by various workers right from the year 1828-30 (Brongniart) to 2010 (Pal et al, 2010). The attempt is creditable but it is better if fossils are examined physically before coming to any conclusion.…”
Section: Insect Herbivorymentioning
confidence: 99%
See 1 more Smart Citation
“…These features are attributed to surface feeding of insect (Labandeira & Phillips, 1996;Srivastava & Agnihotri, 2011). Slater et al (2014) have observed probable presence of external foliage damage and other types of insect herbivory in Indian Gondwana floral assemblages described by various workers right from the year 1828-30 (Brongniart) to 2010 (Pal et al, 2010). The attempt is creditable but it is better if fossils are examined physically before coming to any conclusion.…”
Section: Insect Herbivorymentioning
confidence: 99%
“…The Late Permian Raniganj and Kamthi floras show the presence of insect damaged leaves, galls, oviposition marks and coprolite-like structure (Chauhan et al, 1985;Banerjee & Bera, 1998;Slater et al, 2014). Late Permian flora of Maitur Formation (Pal et al, 2010) has also been found to contain insect nibbled leaf margin (Slater et al, 2014). Early Cretaceous flora of Rajmahal contains distinct evidence of insect herbivory (Banerji, 2004;Srivastava & Krassilov, 2012).…”
Section: Introductionmentioning
confidence: 99%